Analisa Perancangan Sistem Informasi Pelaporan Fasilitas Umum dan Informasi Pembuatan E-KTP Untuk Masyarakat - Mohammad Puji Hari Setiawan; Fajar Masya (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2020)
Public facilities provided by the government are a tool for the community to carry out daily activities. From the start of pedestrians, roads, traffic lights to landfills. In addition to public facilities, information on making E-KTP is also very helpful for the community in finding information on making E-KTP to make it easier. If there is damage or misuse of the facility, a corrective action or a quick solution is needed so that it can be reused. With the ignorance of the government or the surrounding apparatus regarding the damage or misuse it can cause disruption of the activities that occur every day. With the web-based application that I call "Report It" it can help the government or the surrounding apparatus to find out about damage or misuse of public facilities, rubbish piles that need cleaning, roads that need to be repaired, and also know which facilities should be held or increase again. So that the handling of justification will be faster. Information on making E-KTP will also help the community in finding information on making their E-KTP, so they do not bother to look for that information in the authorized sub-district office. The system is designed using the waterfall method, UML modeling, data structure modeling and the relationship between ERD data while the programming language used is PHP, and for the database it uses MySQL.